Economic and non-economic determinants of retirement intentions. Empirical evidence from Poland - Swacha-Lech, Magdalena; Kowalczyk-Rólczyńska, Patrycja; Jurek, Łukasz (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The aim of the study was to identify and evaluate the factors that have a significant impact on the intention to retire as soon as possible among workers in Poland. Methodology: To achieve this goal the structural equation modelling (SEM) method was used. The data came from the authors’ own study conducted in Poland at the end of 2021 using the computer assisted web interview (CAWI) method on a representative group of employees aged 50 and above. The authors selected a range of potential predictors, including demographic, economic, workplace-related, and psychological. Results: The results showed that personal factors and anticipated level of income in retirement positively influence the intention to retire as soon as possible, whilst education, monthly income, income voluntarily saved for retirement, good working conditions and positive attitudes towards retirement have a negative impact. Implications and recommendations: The results of the study, conducted among the Polish population aged 50+ living in one of the fastest developing countries of Central and Eastern Europe, may contribute to research conducted in other European countries. The implementation of a similar study by other researchers will allow for comparison and may form the basis for recommendations relevant to an ageing Europe and a lower burden on public finances in each country. Originality/value: To the best of the authors’ knowledge, this is the first such analysis for Poland. The extensive catalogue of variables adopted for the study facilitated an indepth analysis of the factors influencing the intention to retire as soon as possible.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 137-153
Keywords: retirement decisions; retirement intentions; personal characteristics; work environment; pension system